2017 IEEE International Conference on Communications (ICC) 2017
DOI: 10.1109/icc.2017.7997168
|View full text |Cite
|
Sign up to set email alerts
|

AoD-adaptive subspace codebook for channel feedback in FDD massive MIMO systems

Abstract: Channel feedback is essential in frequency division duplexing (FDD) massive multiple-input multipleoutput (MIMO) systems. Unfortunately, previous work on multiuser MIMO has shown that the codebook size for channel feedback should scale exponentially with the number of base station (BS) antennas, which is greatly increased in massive MIMO systems. To reduce the codebook size and feedback overhead, we propose an angle-of-departure (AoD)-adaptive subspace codebook for channel feedback in FDD massive MIMO systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 27 publications
0
75
0
Order By: Relevance
“…In [2], [3], the authors utilized the slowly changing feature of the space and estimated the downlink CSI from the downlink training process. Numerical results in [4] also showed that a significant overhead reduction can be achieved via the partial support information obtained from the uplink.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], [3], the authors utilized the slowly changing feature of the space and estimated the downlink CSI from the downlink training process. Numerical results in [4] also showed that a significant overhead reduction can be achieved via the partial support information obtained from the uplink.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we will discuss the quantization error, which is different from that in [6] and [9] due to the specific distribution of the equivalent channel h e k . In the rest of this paper, we can omit the subscript k without loss of generality, where h e , A, and P denote the equivalent channel, the steering matrix, and the number of dominant paths per user, respectively.…”
Section: B Performance Analysis Of the Proposed Rdscmentioning
confidence: 99%
“…Finally, the k-th user will quantize the equivalent channel h e k based on the proposed RDSC by finding d k,F k that is closest to h e k , where the index F k is computed as is just a scalar, we follow the widely used assumption that this magnitude h e k can be fed back to the BS perfectly [6], [7], [9]. The codebook index F k can be fed back using B bits.…”
Section: A Proposed Rdscmentioning
confidence: 99%
See 2 more Smart Citations